Propriétés optoélectroniques des superréseaux ordonnés et désordonnés types (III-V) à base d’Arsenic - Bendahma Fatima (My University, 2015)
During this work, the study was focused on the optoelectronic properties of ordered and disordered superlattices (SR's) based Arsenic types (III-V). We discuss the impact of the aluminium concentration on the laser wave length and the resonant tunnelling time (RTT) of random dimer and trimer barrier AlxGa1-xAs superlattices. Such systems consist of two different structures randomly distributed along the growth direction, with the additional constraint that the barriers of one kind appear in doubly or triply. An explicit formula is given for evaluating the transmission coefficient of (SL’s) with intentional correlated disorder. The method is based on Airy function formalism and the transfer-matrix technique. The two proposed profils improve the devices performance by increasing electron concentration, which allows us to perform high-speed optoelectronic devices due to their very short response time on the order of femtosecond. Our study shows that the modulation of the wavelength can be obtained by the variation of aluminium concentration. The obtained wavelengths of the studied structures allow to have very promising devices operating in the mid- infrared domain.
Keywords: Superlattices; dimer; trimer; Transfer-matrix; laser.